Navigating the neuronal recycling bin: Another look at huntingtin in coordinating autophagy - Thomas J. Krzystek; Shermali Gunawardena (Autophagy Reports)
Neurons, as post–mitotic and long–lived cells, rely heavily on autophagy to maintain cellular homoeostasis and ensure proper function. Huntingtin (HTT), a protein central to Huntington’s disease (HD), has emerged as a putative multifunctional regulator within the neuronal autophagy–lysosome pathway. This review explores normal HTT’s multifaceted role in neuronal autophagy, from its potential involvement in autophagy induction, its capacity to influence cargo recognition and autophagosome formation, and its contribution to autophagosome–lysosome fusion and transport. We also discuss the unique challenges that neurons face in maintaining proteostasis through autophagy, emphasising the need for specialised mechanisms like axonal transport of autophagosomes and distinct regulatory pathways. Furthermore, we highlight the spatial and temporal regulation of neuronal autophagy, particularly in the context of ageing and neuronal maturation, underscoring the importance of understanding HTT’s role in different neuronal states. By elucidating the intricate relationship between HTT and neuronal autophagy, this review aims to shed light on specific mechanisms of action in autophagy that can be disrupted in neurodegenerative diseases including HD.